FAKTOR-FAKTOR YANG MEMPENGARUHI PARTISIPASI LANSIA DALAM MENGIKUTI PROGRAM VAKSINASI COVID-19 DI PUSKESMAS ANDALAS - Mona Ariestia (Akper Kesdam I/Bukit Barisan Padang, 2021)
The COVID-19 disease caused by the SARS-CoV-2 (Severe Acute Respiratory SyndromeCoronavirus-2) virus has become a serious health problem that needs to be addressed. WHOhas declared the COVID-19 pandemic a public health emergency of international concern.People who are easily infected with COVID-19 are the elderly. To prevent infection withCOVID-19, vaccination can be done. Method This research is an analytical observationalstudy with a cross sectional study design. The research data used was a questionnaire for 150elderly with categories of 77 elderly who did not participate and 73 elderly who participatedin the COVID-19 vaccination program in the period November-December 2021. The samplein this study was a population that met the inclusion and exclusion criteria. The dataobtained were then analyzed using univariate analysis and bivariate analysis. Results Thereis a relationship between sex (p=0.000), age (p=0.003), occupation (p=0.004), education(p=0.001), knowledge (p=0.000), attitude (p=0.000), distance of residence (p=0.000) Jurnal Ilmiah Cerebral MedikaVol.3.No 2 (2021)p-ISSN :2657-2435e-ISSSN:2721-31452p=0.000), accessibility (p=0.003), family support (p=0.000), socialization (p = 0.000) andsources of information (p=0.003) had a significant relationship with elderly participation inthe COVID-19 vaccination program at the Merdeka Health Center. . Meanwhile, theparticipation of the JKN program (p=0.898) did not have a significant relationship with theparticipation of the elderly in the COVID-19 vaccination program at the Merdeka HealthCenter. The COVID-19 disease caused by the SARS-CoV-2 (Severe Acute Respiratory SyndromeCoronavirus-2) virus has become a serious health problem that needs to be addressed. WHOhas declared the COVID-19 pandemic a public health emergency of international concern.People who are easily infected with COVID-19 are the elderly. To prevent infection withCOVID-19, vaccination can be done. Method This research is an analytical observationalstudy with a cross sectional study design. The research data used was a questionnaire for 150elderly with categories of 77 elderly who did not participate and 73 elderly who participatedin the COVID-19 vaccination program in the period November-December 2021. The samplein this study was a population that met the inclusion and exclusion criteria. The dataobtained were then analyzed using univariate analysis and bivariate analysis. Results Thereis a relationship between sex (p=0.000), age (p=0.003), occupation (p=0.004), education(p=0.001), knowledge (p=0.000), attitude (p=0.000), distance of residence (p=0.000) Jurnal Ilmiah Cerebral MedikaVol.3.No 2 (2021)p-ISSN :2657-2435e-ISSSN:2721-31452p=0.000), accessibility (p=0.003), family support (p=0.000), socialization (p = 0.000) andsources of information (p=0.003) had a significant relationship with elderly participation inthe COVID-19 vaccination program at the Merdeka Health Center. . Meanwhile, theparticipation of the JKN program (p=0.898) did not have a significant relationship with theparticipation of the elderly in the COVID-19 vaccination program at the Merdeka HealthCenter.